The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill - Yayi Wahyu Ilmillahdini; Puji Sumarsono (University of Muhammadiyah Malang, 2014)
The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill